Harnessing Problem-Based Learning to Strengthen Interprofessional Education: Addressing Health Disparities and Sensitive Topics. - Porter, Andrew; Falcon, Ashley; Matsuda, Yui; Foronda, Cynthia; Graefe, Beck (Nursing Education Perspectives (Wolters Kluwer Health), 2026)
This study evaluates the impact of problem-based learning (PBL) in strengthening interprofessional education to address health disparities. Forty-seven nursing and public health students participated in a course using PBL to tackle complex issues such as race, poverty, and sexual orientation. Pre- and post-surveys assessed communication, critical thinking, and teamwork skills. Results showed significant improvements across all domains, with the greatest gains in communication proficiency and critical thinking. The findings suggest that PBL is an effective pedagogical tool for preparing health professionals to engage in difficult conversations and collaborate to address systemic health disparities.